Bioefficacy of Aspergillus niger isolates against Soil Borne Pathogens of Field Pea - Rashmi Nigam; Jaibir Tomar (Annals of Agricultural Research, 2022)
Three pathogens viz. Fusarium oxysporumf sp. pisi, Rhizoctonia solani and Pythium ultimum were in vitro tested for their sensitivity towards the isolates of antagonists Aspergillus niger. Results showed that Aspergillusniger proved potential in vitro test through inhibiting the mycelial growth. The antagonists grew on the mycelial of all the test pathogens and reduced the mycelial growth of Fusarium oxysporumf sp. pisi, Rhizoctonia solani and Pythium ultimum. Among all isolates of Aspergillus niger, isolates An1 exhibites significantly the highest antagonistic potential against Fusarium oxysporum, Rhizoctonia solani and Pythium ultimum there by resulting in 68.00, 65.85 and 65.94 percent growth inhibition, respectively over control.The inhibition of the soil borne pathogens is due to the antagonistic effects of locally isolated A. niger.